On Averting Negative Emotion: Remedying the Impact of Shifting Expectations - Cho, Cecile K.; Cho, Theresa S. (Frontiers in Psychology, 2018)
This paper examines how people anticipate negative emotions when faced with an uncertain outcome and try to manage their expectations. While extant research streams remain equivocal on whether managing expectations always succeeds, this research examines situations in which setting a low expectation can have an adverse emotional impact and suggests ways to alleviate this negative consequence. Using goal setting and a false-feedback paradigm, we show that, although individuals who set low goals to manage expectations can end up feeling more disappointed than those who set high goals (study 1), this negative impact can be avoided when individuals are reminded of their initial goals at feedback, or made aware of inaccuracies in forecasting their future emotion (studies 1 and 2).